2021
DOI: 10.1177/2050313x211002313
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial infusion of autologous bone marrow mononuclear cells combined with intravenous injection of cerebrolysin in the treatment of middle cerebral artery ischemic stroke: Case report

Abstract: We present a patient with severe middle cerebral artery occlusion who received an intra-arterial infusion of autologous bone marrow stem cells combined with Cerebrolysin IV. The patient was evaluated before and after treatment using the National Institutes of Health Stroke Scale, the Medical Research Council Muscle Scale, Modified Brunnstrom Classification, Barthel Index and modified Rankin Scale. After the therapy, the patient showed good outcome with functional as well as neurological improvements especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…International Publisher confer some therapeutic effects, the effects were not significant [24][25][26]. Attempts have been made to develop novel MSC-based methods for the treatment of IS, such as genetically-modified MSCs, and use of preconditioning, electrical stimulation, and ultrasonic stimulation.…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…International Publisher confer some therapeutic effects, the effects were not significant [24][25][26]. Attempts have been made to develop novel MSC-based methods for the treatment of IS, such as genetically-modified MSCs, and use of preconditioning, electrical stimulation, and ultrasonic stimulation.…”
Section: Ivyspringmentioning
confidence: 99%
“…For example, in the harsh microenvironment of stroke (inflammation storm, oxidative stress), isolated MSCs gradually lose their homing ability to the lesion 23 . In clinical trials, although MSC therapy was shown to be safe and confer some therapeutic effects, the effects were not significant 24 - 26 . Attempts have been made to develop novel MSC-based methods for the treatment of IS, such as genetically-modified MSCs, and use of preconditioning, electrical stimulation, and ultrasonic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Phase I and II clinical trials for the IA autologous bone marrow mononuclear cell infusion in stroke have already been published. The published trial outcome show the safety of autologous bone marrow mononuclear cells administration in sub-acute ischemic stroke [ 159 , 163 ], non-acute ischemic stroke [ 160 , 164 ], and moderate to severe acute middle cerebral artery strokes [ 159 , 165 , 166 ]. However, the analysis of the efficacy of stroke therapy with the IA injection of bone marrow mononuclear cells did not show prominent improvement in comparison with the placebo [ 159 , 163 ], although several trials have shown some improvement in patients receiving cell therapy [ 164 , 165 ].…”
Section: Clinical Trials Of the Intra-arterial Msc Infusion In Patients With Ischemic Strokementioning
confidence: 99%
“…However, the analysis of the efficacy of stroke therapy with the IA injection of bone marrow mononuclear cells did not show prominent improvement in comparison with the placebo [ 159 , 163 ], although several trials have shown some improvement in patients receiving cell therapy [ 164 , 165 ]. One study showed the safety and some efficacy of intra-arterial transplantation of allogeneic umbilical cord MSCs (UC-MSC) in patients with ischemic and hemorrhagic strokes [ 166 ]. Thus, so far, clinical trials failed to fully reveal the therapeutic potential of stem cells, as it has been done in animal models of stroke.…”
Section: Clinical Trials Of the Intra-arterial Msc Infusion In Patients With Ischemic Strokementioning
confidence: 99%